2012
DOI: 10.1016/j.nut.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and resting energy expenditure in patients with chronic hepatitis C before and during standard treatment

Abstract: Our study of patients with hepatitis C treatment showed that these patients had significant weight loss and this was not associated with changes in energy expenditure. However, we observed a significant decrease in energy intake, pointing to a possible need for intervention measures to decrease the damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Therefore, before starting antiviral therapy, it is better to improve some metabolic disorders including obesity and insulin resistance by diet therapy and exercise therapy. After starting IFN-based therapy, body weight decreases due to decreased appetite and some digestive symptoms in many patients [28, 29]. A recent study showed that resting energy expenditure did not increase during IFN-based antiviral therapy, and weight loss during the therapy was ascribed to a decrease in energy intake [29].…”
Section: Nutrition Therapy For Chc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, before starting antiviral therapy, it is better to improve some metabolic disorders including obesity and insulin resistance by diet therapy and exercise therapy. After starting IFN-based therapy, body weight decreases due to decreased appetite and some digestive symptoms in many patients [28, 29]. A recent study showed that resting energy expenditure did not increase during IFN-based antiviral therapy, and weight loss during the therapy was ascribed to a decrease in energy intake [29].…”
Section: Nutrition Therapy For Chc Patientsmentioning
confidence: 99%
“…After starting IFN-based therapy, body weight decreases due to decreased appetite and some digestive symptoms in many patients [28, 29]. A recent study showed that resting energy expenditure did not increase during IFN-based antiviral therapy, and weight loss during the therapy was ascribed to a decrease in energy intake [29]. Although there are no guidelines on how nutrition therapy should be conducted, a decrease in quality of life or malnutrition must be prevented for avoiding an interruption in antiviral therapy.…”
Section: Nutrition Therapy For Chc Patientsmentioning
confidence: 99%
“…According to medical reports, in addition to the therapeutic objective, side effects are often associated with standard therapy. Some of these side effects include depression, anxiety, psychosis, cognitive impairment and body weight (BW) loss [3][4][5][6]. The exact contributions of each component of combined therapy to the side effects have not been elucidated, but there is a view that they are mainly related to interferon alpha [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Fioravante et al demonstrated that the weight loss during treatment was accompanied by a significant decrease in energy intake as assessed by 24-h recall. However, there was no change in resting energy expenditure19.…”
Section: Discussionmentioning
confidence: 87%